(untitled) (Estudios de Historia de España, 2021)
The article provides a prospect of the social policy carried out in Spain during the last three centuries, in order to verify the duration and the tortuous path from the private to the public social care. It analyzes how the private assistance has a significant weight that imposes the satisfaction of the interests of the assistants, called “Mateo effect”. Finally, it goes through the historical recovery of the private initiative, which was institutionalized in the form of volunteering and led to the Third Sector of the assistance, made up of non-governmental and non-profit organizations, integrated by volunteers, which complement the Welfare State. They are in a third position and claim to be nor private neither public; but some consider them as not totally neutral and closer to the private than to the public.